Interpretasi Kontekstual Ayat Hutang (Dain) dan Relevansinya terhadap sistem transaksi keuangan modern masa kini: Kajian Hermeneutika Double Movement Fazlur Rahman - Masodi Masodi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Fazlur Rahman, a modern Islamic thinker, offers the Double Movement hermeneutic method as an approach to understanding the texts of the Qur'an. This method emerged as Rahman's critique of the classical interpretation method which is considered partial and atomistic in interpreting the Qur'an. This study will focus on two research questions, namely How is the Meaning of